Preferential retrotransposition in aging yeast mother cells is correlated with increased genome instability - Patterson, Melissa N. (DNA Repair (Amst), 2015)
Retrotransposon expression or mobility is increased with age in multiple species and could promote genome instability or altered gene expression during aging. However, it is unclear whether activation of retrotransposons during aging is an indirect result of global changes in chromatin and gene regulation or a result of retrotransposon-specific mechanisms. Retromobility of a marked chromosomal Ty1 retrotransposon in Saccharomyces cerevisiae was elevated in mother cells relative to their daughter cells, as determined by magnetic cell sorting of mothers and daughters. Retromobility frequencies in aging mother cells were significantly higher than those predicted by cell age and the rate of mobility in young populations, beginning when mother cells were only several generations old. New Ty1 insertions in aging mothers were more strongly correlated with gross chromosome rearrangements than in young cells and were more often at non-preferred target sites. Mother cells were more likely to have high concentrations and bright foci of Ty1 Gag-GFP than their daughter cells. Levels of extrachromosomal Ty1 cDNA were also significantly higher in aged mother cell populations than their daughter cell populations. These observations are consistent with a retrotransposon-specific mechanism that causes retrotransposition to occur preferentially in yeast mother cells as they begin to age, as opposed to activation by phenotypic changes associated with very old age. These findings will likely be relevant for understanding retrotransposons and aging in many organisms, based on similarities in regulation and consequences of retrotransposition in diverse species.